The Age Distribution of Detrital Zircons in Quartzites from the Toodyay-Lake Grace Domain, Western Australia: Implications for the early Evolution of the Yilgarn Craton - Pidgeon, Robert; Wingate, Michael; Bodorkos, S.; Nelson, D. (American Journal of Science, 2010)
Evidence for the early history of the Archean Yilgarn Craton has been largely obliterated by the craton-wide emplacement of granitic rocks at c. 2650 Ma. However, detrital zircons from rare, c. 3.1 Ga quartz-rich metasediments preserved in the Yilgarn Craton provide an opportunity to investigate the age structure and composition of the pre-existing basement and therefore provide a valuable record of the early history of crustal components that combined to form the Yilgarn Craton. In this report we present the results of an ion microprobe (SHRIMP) U-Pb geochronological study of detrital zircons from six samples of quartzites from the Toodyay-Lake Grace Domain (TLGD) in the South West Terrane of the Yilgarn Craton. Consistent features in the detrital zircon age spectra in all samples demonstrate a basic uniformity in the composition of the source rocks. The results suggest a provenance dominated by c. 3350 to 3200 Ma granitic rocks with an age peak at c. 3265 Ma. No granites of this age have so far been identified in the south-western part of the Yilgarn Craton, although c. 3280 Ma granites occur in the Narryer Terrane in the northwestern corner of the craton. A second consistent zircon age component suggests an earlier episode of granite emplacement at c. 3500 to 3400 Ma. A minor component of material contributed zircons as old as 3850 Ma to the pre-2650 Ma basement of the proto-Yilgarn Craton. Our zircon age results suggest that the provenance of the TLGD was different from that of the c. 3.1 Ga quartzites and metaconglomerates from Mt Narryer and the Jack Hills in the Narryer Terrane and from the Maynard Hills greenstone belt in the Southern Cross Domain. Although the zircon age spectra are not consistent with an origin from presently exposed gneisses from the Narryer Terrane, the presence of granite and pegmatite in the Narryer Terrane close in age to the main zircon age peak in the TLGD sediments suggests a possible connection. Some detrital zircons in the TLGD have been altered hydrothermally or overgrown by zircon rims during the c. 2650 Ma sillimanite-grade metamorphism that affected the southern part of the TLGD.